Classification of three-generation models by orbifolding magnetized T2 × T2. (23rd February 2021) - Hoshiya, Kouki; Kikuchi, Shota; Kobayashi, Tatsuo; Ogawa, Yuya; Uchida, Hikaru
Abstract: We study orbifolding by the $\mathbb{Z}_2^{\rm (per)}$ permutaion of $T^2_1 × T^2_2$ with magnetic fluxes and its twisted orbifolds. We classify the possible three-generation models which lead to non-vanishing Yukawa couplings on the magnetized $T^2_1 × T^2_2$ and orbifolds including the $\mathbb{Z}_2^{\rm (per)}$ permutation and $\mathbb{Z}_2^{\rm (t)}$ twist. We also study the modular symmetry on such orbifold models. As an illustrating model, we examine the realization of quark masses and mixing angles.